Collaborative decision-making and sustainable food security: Rethinking the role of indigenous knowledge and farming practices in Uganda - Tweheyo, Robert; Wambede, Muhammud Nabalegwa; Nyangoma, Anicent (Universitas Airlangga, 2024)
The paper examines the role of stakeholders' joint decision-making in exploiting indigenous knowledge and practices of local people to achieve sustainable food security. It assesses ways in which the collaboration of farmers and stakeholders in Uganda enhances knowledge sharing, which is vital for sustainable food security. Specifically, the study assesses the significance of indigenous knowledge in enhancing food security, the importance of joint decisions of stakeholders (farmers, community development workers, and extension workers) to food security enhancement, and the factors farmers consider when choosing indigenous/modern practices for enhancing food security. Qualitative methods of data collection were used to get views and experiences of the selected sixty-seven rural farmers in their efforts to enhance food security. Findings reveal that collaboration between farmers and stakeholders is vital for providing opportunities of sharing knowledge and experience and for determining the right combination of practices that enhance sustainable food security. The study recommends designing guidelines for routine monthly meetings between farmers and key stakeholders to share knowledge and experiences that are relevant to enhancing sustainable food security.